Strategy to Build a Brand Image of Feminine Hygiene "Gendes" through Doctor's Educational Videos on Tiktok - Pasha, Dea Amelia; Swasty, Wirania (Journal La Sociale, 2025)
The phenomenon of overclaim, which was first popularized by the TikTok account "Doctor Detective", has attracted public attention because it has dared to reveal facts based on the results of a skincare pregnancy laboratory test. The issue of overclaim can be a weapon in the brand image of a feminine hygiene whose existence is much more sensitive because it is related to the care of the reproductive organs. Therefore, this study aims to produce a strategy in building the brand image of "Gendes" as a sample, through the visual element in content of the doctor's TikTok video matrix to make it more attractive and reliable as one of the feminine hygiene. So that the target market is right on target, including educational campaigns about reproductive health care, especially for married women and children. The research method used is qualitative with a case study approach, involving data collection techniques such as literature studies, observations, documentation, interviews, and focus group discussions. The results of the study show that this strategy can improve the brand image of "Gendes" to be more reliable, because it is built from a strategy with a focus on visualization of the content of the doctor's video matrix that is convincing, credible and impresses the audience. In conclusion, a strategy to build a brand image when partnering with doctors is needed to build awareness, consideration, decision and retention/loyalty in the TikTok video visual container so that the content and safety are more reliable for consumers of the "Gendes" brand as a feminine wash product in accorandce with TikTok and health rules.